(untitled) (American Journal of Islam and Society, 1986)
W. Montgomery Watt, Muhammad at Mecca (Oxford: At the Clarendon Press, 1953), 192 pp., and Muhammad at Medina (Oxford: At the Clarendon Press, 1956), 417 pp. Maxime Rodinson, Mahomet (France: Club francais du livre, 1961), 378 pp., English translation by Anne Carter Muhammad, (London, The Penguin Press, 1971), with New Introduction and Foreward (New York, Pantheon Books, 1980), 363 pp. Duncan Black MacDonald, Aspects of lslam (New York, The Macmillan Company, 1911), 375 pp. The biography (Sira) of the Prophet Muhammad (SAAW) has attracted the interest of scholars in both the Islamic world and the West for centuries. Vast literature exists on the subject in Arabic and in numerous European and Asian languages. The reasons for this interest are numerous and complex, ranging from religious to ideological and political motivations. The earliest Arabic biographies of the Prophet date back to the second century of the Hijra/ eighth century A.C. The Sira of Ibn-Ishaq and that of Ibn-Hisham (based on the former) have had the greatest influence on the vast literature concerning the Sira. Yet there are Siras dating back to the sixth and seventh centuries A.H. which are still in the form of manuscripts waiting to be edited. The Qur‘an and the sayings and actions of the Prophet (Hadith) are the two most important sources for studying the Prophet’s Sira. The Prophet’s biography has attracted great interest also in the West. During the Middle Ages, the Prophet was the object of attack by Christian priests and propagandists, whom we might call the original Orientalists. He was denigrated, his figure was deformed, and he was given insolent names like ...